The art of feminist-queering the museum : gate-leaking - Grácio, Rita (2021)
This paper takes part in the ongoing debate around how museums have begun to address LGBTQI+ and feminist issues in the 21st century. While Portugal is a particularly interesting country to consider, given that it has passed some of the most advanced legislation on LGBTQI+ rights in Europe (Santos 2012), this progressivism is not reflected in Portuguese museum practices, given that gender museology has been slow to emerge (Vaquinhas 2014). After briefly contextualising initiatives addressing gender in Portuguese art museums, we present as a case study Trazer a margem para o centro (Bringing the Margin to the Centre), a series of three talks hosted by the Berardo Collection Museum, which is considered Portugal’s primary modern and contemporary art museum. Unlike previous initiatives in art museums, which were museum-led, the series of talks was led by the small intersectional feminist collective FACA. A sociologist (Rita Grácio) and the three members of FACA (Andreia Coutinho, Laura Falé and Maribel Sobreira) designed and conducted the three talks that constitute the initiative Bringing the Margin to the Centre. Grácio designed and conducted the qualitative study of the audiences that attended Bringing the Margin to the Centre. This study consisted of participant observation at the event series, at which an adapted version of the Personal Meaning Mapping technique (Falk and Storksdieck 2005) was applied; semi-structured phone interviews with participants were then conducted after the event (Falk and Dierking 2011). The main findings show this event raised awareness among cisgender visitors with heteronormative perspectives and provided a space for counter-narratives of the queer community, showing the role of collective curatorial activism and museums in promoting gender equality and inclusiveness, if acting as gate-leakers, rather than as gatekeepers. Hence, museums can provide lessons to other organisations interested in promoting diversity and inclusion.